THE EFFECTIVENESS OF TEACHING THE SUBJECT OF FOLK PEDAGOGY AS A PRESSING EDUCATIONAL ISSUE (American Journal of Pedagogical and Educational Research, 2025)
This article examines the effectiveness of teaching the subject of folk pedagogy in higher education as a pressing pedagogical issue. Utilizing a mixed-methods approach, the study incorporates surveys, interviews, and experimental classes involving both students and instructors. Findings indicate low student engagement and limited instructor access to modern tools when traditional teaching methods are used. However, innovative strategies such as digital storytelling, ethnographic assignments, and QR-coded folklore archives significantly enhanced learning outcomes and student motivation. The article proposes strategic models and pedagogical solutions for modernizing the instruction of folk pedagogy, integrating technology, interactivity, and cultural relevance. In conclusion, folk pedagogy is positioned not only as a means to preserve cultural heritage but also as a vital tool for developing moral reasoning and civic values among learners.